Discrete SnO2 Nanoparticle‐Modified Poly(3, 4‐Ethylenedioxythiophene):Poly(Styrenesulfonate) for Efficient Perovskite Solar Cells. Issue 10 (5th July 2019) - Jia, Pengcheng; Bi, Wentao; Huang, Xin; Li, Ling; Gong, Wenwen; Tang, Yang; Zhao, Di; Hu, Yufeng; Lou, Zhidong; Teng, Feng; Cui, Qiuhong; Hou, Yanbing
Abstract : Poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is the most widely used hole transport materials for perovskite solar cells (PVSCs) with a p‐i‐n structure. However, the solar cells based on PEDOT:PSS show a low photoconversion efficiency due to the poor crystallinity of a perovskite film on it. Besides, the acidity of PEDOT:PSS performance critically influences the long‐term stability of PVSCs. Herein, a layer of the discrete SnO2 nanoparticle film is deposited on the surface of PEDOT:PSS to modify the surface of the PEDOT:PSS film. This discrete SnO2 nanoparticle film acts as the buffer layer between the PEDOT:PSS and MAPbI3, which not only improves the crystallization of the quality of the perovskite film, but also provides a selective‐carrier pathway to enhance the extraction of holes and to block the diffusion of electrons. The SnO2 modified devices show a power conversion efficiency of 18.04%, with a great improvement compared with the 12.24% efficiency of PEDOT:PSS only devices. This work demonstrates that it is possible to enhance the performance of PVSCs via n‐type nanoparticle modification of hole transport layer and provides a new guidance for PVSCs interface modification engineering. Abstract : Perovskite solar cells (PVSCs) with discrete SnO2 nanoparticle modification layers are constructed via spin coating the SnO2 dispersions on poly(3, 4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS). The discrete SnO2 nanoparticle film let holes pass and block electrons to diffuse toward PEDOT:PSS, which enhances the extraction efficiency, leading to an increase in a power conversion efficiency of p‐i‐n‐type PVSCs.